Lapbook Berbasis Bahan Daur Ulang: Inovasi Media Pembelajaran di Sekolah Dasar - Nurdin, Andi Nurdiah; Salmilah, Salmilah; Hisbullah, Hisbullah (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
This research is entitled Developing Lapbook Media Based on Recycled Materials, Material for Changes in the Form of Objects for Class IV Students at UPT SDN 115 Lanosi, Burau District, East Luwu Regency. This research aims to determine the analysis of the needs for developing lapbook media, knowing the process of developing lapbook media, knowing the validity, and knowing the practicality of using lapbook media based on recycled materials, materials that change the shape of objects in Class IV students at UPT SDN 115 Lanosi, Burau District, East Luwu Regency. This research uses a type of development research or Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The object of this research is laptop media based on recycled materials that change the shape of objects. Meanwhile, the subjects were teachers and students of class IV UPT SDN 115 Lanosi, totaling 22 students. The data collection techniques used were observation, interviews, documentation and giving questionnaires to educators and students. The data obtained was then analyzed qualitatively and quantitatively. The results of the research show that from the results of the needs analysis in ongoing learning new innovations are needed regarding learning media in the form of lapbook media based on recycled materials on material that changes the shape of objects. And for the validity of the lapbook media, it was validated by 2 experts, namely media experts with a score of 94% (very valid category), and material experts with a score of 94% (very valid category), the average percentage of scores from the two validators was 94% ( very valid category). For the practicality test, the results obtained from students were 98% and from educators it was 95%. This research produces a laptop media product that meets the criteria of being very valid and very practical so it is suitable for use.